Screening of Cowpea Genotypes for Growth, Yield and Cowpea Mosaic Virus Incidence - Mal, Dipika; Datta, Suchand; Tulshidas, Bhaisare Pranali; Chowdhury, Apurba; Islam, Siddikul (Bangladesh Journal of Botany, 2022)
Eighteen cowpea genotypes against cowpea mosaic virus disease under zero tillage condition were screened during pre Kharif season of 2013, 2014 and 2015 at the field in Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal.Significant variation was observed for different genotypes with respect to cowpea mosaic virus, growth, yield and qualities. Highest pod yield was recorded in Kashi Kanchan (16.42 t/ha) which was statistically at par with Kanak (16.30 t/ha). Genotypes Bidhan Barbati 1, Bidhan Barbati 2, Kaberee and Pusa Komal were recorded without disease incidence i.e.immune while, Kanak, Pusa Phalguni Gold and Lafa Charulata exhibited highly resistance against cowpea mosaic virus. It was observed that cowpea mosaic virus incidence was negatively correlated with chlorophyll content, number of pods/plant, pod yield, leaf phenol content and leaf peroxidase content whereas, it was positively correlated with canopy temperature, days to flowering and first harvest. Bangladesh J. Bot. 51(4): 817-820, 2022 (December)